Anthocyanins: Potential Therapeutic Approaches towards Obesity and Diabetes Mellitus Type 2 - Denise Franco-San Sebastián; Samary Alaniz-Monreal; Griselda Rabadán-Chávez; Natalia Vázquez-Manjarrez; Marcela Hernández-Ortega; Gabriela Gutiérrez-Salmeán (Molecules, 2023)
Overweight and obesity are present in about three-quarters of the adult population in Mexico. The inflammatory mechanisms subjacent to visceral white adipose tissue are accountable for the initiation and development of cardiometabolic alterations, including type 2 diabetes. Lifestyle changes are pillars within its therapeutics and, thus, current dietary modifications should include not only hypocaloric prescriptions with balanced macronutrient intake, preferably by increasing the amount of whole grains, fruits, vegetables, nuts and legumes, but in concomitance, bioactive substances, such as anthocyanins, have been correlated with lower incidence of this disease.